Wideband ring resonator bandpass filter (WRRBPF) / Nur Fatehah Asri - Asri, Nur Fatehah (2009)
Micrdstrip Bandpass Filter (BPF) is one of the essential devices in communication system either at the transmitter and receiver. Thus, the quality of BPF is very importantThis work highlights the design, simulation and the fabrication of a ring resonator bandpass filter for wideband application. The operating frequency range is 1- 9 GHz with the center frequency of 5.77GHz using Rogers Duroid 4350 substrate with, ^ = 3.48. The design, simulation and EM analysis were carried out using commercial software. Measurements of the prototype were carried out using Vector Network Analyzer (VNA). It was observed that the measured and the simulation results were quite similar.